The effect of postharvest ultraviolet irradiation on the content of antioxidant compounds and the activity of antioxidant enzymes in tomato - Dyshlyuk, Lyubov (Heliyon, 2020)
The effect of different doses of long-wavelength UV-A (320 nm–400nm) irradiation on physicochemical and antioxidant characteristics of tomatoes grown on the territory of the Russian Federation was studied. The obtained results show that this kind of processing does not cause deterioration of qualitative parameters of vegetables (texture, color, soluble solids content, titratable acidity). It was established that the total content of phenolic compounds, carotenoids and flavonoids increases (p-value<0.05) in tomatoes at all the investigated wavelengths (353 nm, 365 nm and 400 nm), while the content of chlorophylls reacts ambiguously: at some wavelengths, it increases, at other, it decreases. The maximum increase in antioxidant activity, as compared to untreated samples, is observed in tomatoe samples irradiated for 360 min within the range of 365 nm. For different types of tomatoes, the increment for common content of phenolic compounds is – 42.9–55.0 %, carotenoids – 24.0–56.0 %, flavonoids – 28.0–33.0 %, β-carotene – 70.9–71.6 %, lycopene – 62.6–69.0 %, lutein – 64.8–72.0 % from original. The studies reveal some potential of post-harvest ultraviolet irradiation (A-range) of tomatoes to increase their antioxidant activity. However, more research is needed to confirm this fact and the possibility to develop some technology.